MODELACION DE FLUJO 1D EN EL RIO UCAYALI - Yzocupe, Victor A. (2006)
It presents the formulation of a one-dimensional numerical model for simulation of flow in the Ucayali river. The model is general and flexible; because it permits to simulate a broad range of flow conditions, such as uniform and non-uniform flow, steady and unsteady. The model does not consider problems of filtration, sediment transport, neither wind. The model is based in the numerical approximation of the governing equations of flow in open channels (Saint Venant’s equations) using the implicit finite difference Preissmann scheme. The dependent variables are the discharge (Q) and the water surface level (Z). The algorithms applied in the segments of the channel plus the boundary conditions compose one system of lineal equations, which is solved using the Double Sweep method. The application is done to a reach of 22 kms of the Ucayali River, near to the Pucallpa city. It presents two tests, one for steady flow and another for non-steady flow, which demonstrate the good performance of the model.